Für Sie gelesen: Aktuelle Studien - Kußmaul, Jörg (PPH, 2020)
Debono A, Corley N, Muraven M. Why Am I Left Out? Interpretations of Exclusion Affect Antisocial and Prosocial Behaviors. The American Journal of Psychology 2020; 133 (1): 63–79